Dampak Tindakan Bullying Terhadap Perkembangan Mental Peserta Didik SMP Negeri 3 Tahuna Barat Kabupaten Kepulauan Sangihe - Christi Koni Mandalika; Julien Biringan; Wua Telly Delly (Tumoutou Social Science Journal, 2026)
Bullying is an increasing phenomenon in this modern era. This study aims to analyze the factors that cause bullying and its impact on the mental development of students. The research method used is qualitative with a case study approach. The results of the study show that bullying in students is caused by internal and external factors, such as lack of character education, and the influence of the surrounding environment. The impact can be an increase in crime, a decrease in character values and a breakdown in social relationships. This study suggests the importance of effective character education and the active role of teachers and parents in preventing bullying in SMP Negeri 3 Tahuna students. This study uses qualitative research methods. The data collection technique was carried out by observation and interviews. Based on the results of this study, it can be concluded that the strategy for handling bullying in students of SMP Negeri 3 Tahuna is carried out by conducting reprimands, education, lectures, approaches, and advice.